Pantun Bajawek dalam Acara Mananti Tando di Binjai Kecamatan Tigo Nagari Kabupaten Pasaman - Yenti, Ermi; Hamidin, Hamidin; Amir, Amril (Universitas Negeri Padang, 2012)
The purpose of this study was to describe (1) the structure of the event Mananti Pantun Bajawek Binjai district Tando Tigo Pasaman Nagari, and (2) the value of education Limerick Event Mananti Bajawek in district Tando Binjai Tigo Pasaman Nagari. The data of this study is the structure of the poem bajawek mananti event in Binjai district Tando Tigo Nagari Pasaman and values ​​education poem bajawek mananti event in Binjai district Tando Tigo Pasaman Nagari. The data sources of this study are oral sources, which are spoken in rhyme bajawek Tando mananti event. Data were collected by observation, recording, interviews, and data processing, the results of the analysis are written in the form of a full report of research results. The findings of the study in the event structure bajawek rhymes with rhyme mananti Tando usual, has sampiran and content and consists of four lines, and talibun ie, six lines, eight rows and ten rows. In addition, the poem was also built by the physical structure and the inner structure. Educational value poem bajawek traditional educational values​​, moral values ​​and values ​​education religious education.